TI_GERICHTE 90.2003.62 vom 7. Februar 2007 , Protezione del nucleo di un comune in quanto bene culturale di interesse cantonale - TI Tribunale d'appello (2007)
Protezione del nucleo di un comune in quanto bene culturale di interesse cantonale